Cognitive Debt and Alzheimer's Disease - Natalie L. Marchant; Robert Howard (2015)
We propose the concept of Cognitive Debt to characterize thoughts and behaviors that increase vulnerability to symptomatic Alzheimer's disease (AD). Evidence indicates that depression, anxiety, sleep disorder, neuroticism, life stress, and post-traumatic stress disorder increase risk for AD, and we suggest they do so by increasing Cognitive Debt. Repetitive negative thinking (RNT), a behaviorally measurable process common to these factors, may drive Cognitive Debt acquisition. RNT transcends disorder-specific definition, encompasses rumination and worry, and is defined by perseverative, negative thought tendencies. Evidence of dysregulated stress responses supports the concept of Cognitive Debt, of RNT as its causal mechanism, and of an interaction with the APOE-ε4 genotype to increase vulnerability to clinical AD, independent from traditional AD pathology. Defining a more specific behavioral profile of risk would enable interventions to be targeted earlier and more precisely at individuals most vulnerable to developing AD. Additionally, modulating RNT could potentially reduce risk of clinical AD. Interventions to reduce RNT are discussed, as are suggestions for future research. For these reasons we submit that the Cognitive Debt model may aid understanding of the psychological mechanisms that potentially increase predisposition to AD.